From Evidence to Clinical Practice: Positive Effect of Implementing a Protein‐Enriched Hospital Menu in Conjunction With Individualized Dietary Counseling. (1st February 2017) - Munk, Tina; Bruun, Nina; Nielsen, Michael A.; Thomsen, Thordis
Abstract : Background: The aim of this study was to investigate if a protein‐enriched menu in conjunction with individualized dietary counseling would increase energy and protein intake in hospitalized patients at nutrition risk compared with providing the protein‐enriched menu as a stand‐alone intervention. Method: Data from medical and surgical hospitalized patients were prospectively collected and compared with a historical intervention group (HIG). Primary outcome was the number of patients achieving >75% of energy and protein requirements. Secondary outcomes included mean energy and protein intake (adjusted for body weight [ABW]), readmission rate, and the number of patients with a baseline intake <50% of energy and protein requirement, who increased to ≥50%. Results: In the intervention group (IG), 92% vs 76% in the HIG reached >75% of energy requirements ( P = .04); 90% in the IG vs 66% in the HIG reached >75% of protein requirements ( p = <0.01). The IG had a significantly higher mean intake of energy and protein compared with the HIG: ABW, 31 kcal kg −1 vs 25 kcal kg −1 ( P < .01) and 1.2 g protein kg −1 vs 0.9 g protein kg −1 ( P < .001). More than 85% of the patients with a baseline <50% of the EP requirement achieved ≥75% of the energy and protein requirement. No difference between readmission rates was found. Conclusion: Providing a protein‐enriched menu in conjunction with individualized dietary counseling significantly increased protein and energy intake in hospitalized patients at nutrition risk.